The Differentiating of Sepsis-Associated and Sepsis-Induced Acute Kidney Injury in Intensive Care Unit Patients - Hotabilardus, Nusi; Anggraeni, Novita (Indonesian Journal of Anesthesiology and Reanimation, 2025)
Introduction: Acute kidney injury (AKI) is a severe and common complication in Intensive Care Unit (ICU) patients, commonly resulting from sepsis. It is associated with elevated mortality, chronic renal failure, and other long-term consequences. Sepsis-associated AKI (SA-AKI) and Sepsis-induced AKI (SI-AKI), a specific sub-phenotype, differ in their underlying pathophysiology. Objective: To examine the distinctions between SA-AKI and SI-AKI, focusing on their pathophysiology, biomarkers for detection, and associated prognoses in critically ill patients. This literature review examines the findings of randomized control trials (RCTs) or meta-analysis studies that learn about biochemical mediators and biomarkers for SA-AKI and SI-AKI, including NGAL, Kim-1, and others, as well as the prognostic impact of these conditions. The literature was gathered from Google Scholar and PubMed using the keywords Sepsis-Associated Acute Kidney Injury, Sepsis-Induced Acute Kidney Injury, Intensive Care Unit, and Sepsis and published within the last ten years (2018–2023). Articles unavailable in the full text were excluded. Review: SA-AKI and SI-AKI are distinct entities within the broader spectrum of sepsis and AKI. SI-AKI involves sepsis-induced direct kidney damage, which differentiates it from other forms of SA-AKI. Various biomarkers such as NGAL, Kim-1, and others are crucial for early detection and differentiation between these conditions. Patients with SA-AKI and SI-AKI usually have a bad outlook. They are more likely to die, be disabled for a long time, and need longer stays in the ICU and hospital than patients with sepsis or AKI alone. Figuring out the underlying pathophysiology and using the right biomarkers can help with early diagnosis and could lead to better outcomes for patients through targeted therapies. Summary: SA-AKI and SI-AKI represent critical complications in ICU patients with sepsis, leading to high mortality and long-term adverse outcomes. Differentiating between these conditions using biomarkers is essential for early detection and management. These patients have a worse prognosis than those with sepsis or AKI alone. This shows how important it is to keep researching and finding better ways to treat these serious complications in critically ill patients.